Epicutaneous immunotherapy with a hypoallergenic Bet v 1 suppresses allergic asthma in a murine model. Issue 12 (25th September 2015) - Siebeneicher, S.; Reuter, S.; Wangorsch, A.; Krause, M.; Foetisch, K.; Heinz, A.; Naito, S.; Reuter, A.; Taube, C.; Vieths, S.; Scheurer, S.; Toda, M.
Abstract: Background: Due to reduced allergic potency, hypoallergenic variants have been suggested as safer and potentially more efficacious alternative to the corresponding wild‐type allergens in allergen‐specific immunotherapy. Here, we aimed at investigating the efficacy of recombinant Bet v 1B2, a hypoallergenic folding variant of Bet v 1, in epicutaneous immunotherapy to suppress asthmatic features using a murine model of birch pollen allergy. Methods and Results: Before, or after sensitization with rBet v 1 plus ALUMW and intranasal challenges with birch pollen extract, BALB/c mice received epicutaneous immunization (EPI) with rBet v 1, or rBet v 1B2 on their depilated back. Prophylactic EPI with rBet v 1B2, but not with rBet v 1, suppressed serum levels of Bet v 1‐specific IgE antibodies and reduced the number of eosinophils and the concentrations of Th2 cytokines in bronchoalveolar lavage. In an established allergic condition, serum levels of Bet v 1‐specific IgE antibodies were similar between PBS‐treated control mice and EPI‐treated mice. However, therapeutic EPI with rBet v 1B2, but not with rBet v 1, significantly suppressed the development of airway inflammation and lung function impairment. Conclusion: This study is the first to show the effect of therapeutic EPI with a recombinant form of a hypoallergenic folding variant on the suppression of asthmatic features. Our results suggest that rBet v 1B2 along with its reduced IgE‐binding capacity could be a preferred therapeutic allergen than wild‐type rBet v 1 in epicutaneous immunotherapy of birch pollen‐induced allergic asthma, in particular due to a lower risk of allergic side effect.